2018
DOI: 10.18632/oncotarget.24536
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 mutation is associated with lower expression of VEGF but not microvessel formation in glioblastoma multiforme

Abstract: IntroductionGlioblastoma multiforme (GBM) represents the most malignant primary brain tumor characterized by pathological vascularization. Mutations in isocitrate dehydrogenases 1 and 2 (IDH1 and IDH2) were observed in GBM. We aimed to assess the intra-tumor hypoxia, angiogenesis and microvessel formation in GBM and to find their associations with IDH1 mutation status and patients prognosis.Methods52 patients with a diagnosis of GBM were included into the study. IDH1 R132H mutation was assessed by RT-PCR from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 72 publications
(89 reference statements)
5
20
1
Order By: Relevance
“…Analysis of CGGA database and clinical practice in our hospital indicated that VEGF expression was significantly lower in IDH1 mut as compared to the wildtype counterpart. Some studies demonstrated that the expression of VEGF was inhibited in the IDH mut gliomas (15,16). These findings supported our results indirectly.…”
Section: Discussionsupporting
confidence: 91%
“…Analysis of CGGA database and clinical practice in our hospital indicated that VEGF expression was significantly lower in IDH1 mut as compared to the wildtype counterpart. Some studies demonstrated that the expression of VEGF was inhibited in the IDH mut gliomas (15,16). These findings supported our results indirectly.…”
Section: Discussionsupporting
confidence: 91%
“…One of these consequences is the increased hypoxia-inducible factor 1-alpha (HIF-1α) that is frequently detected in patients with an IDH-1 mutation ( 19 , 20 ). On the contrary, the proliferation rate (Ki-67) and vascular endothelial growth factor (VEGF) levels are significantly lower in IDH-1 mutated tumors ( 21 , 22 ). However, little is known about the affinity for vasogenic edema in IDH-1 wildtype GBM ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO 2016 classification of gliomas, 108 infiltrative gliomas of all histological grades can be divided into 3 subgroups: IDH1/2-mutant and 1p/19q-non-co-deleted glioblastoma, IDH1/2-mutant and 1p-19q-codeleted glioblastoma and IDH1/2 wildtype glioblastoma. 109,110 Polivka et al 111 describe that IDH1 -mutated glioblastoma is associated with lower levels of VEGF expression than IDH1 wild-type but not with angiogenesis. In our study, 1 glioblastoma sample was IDH1 mutated and we did not observe differences in VEGF levels in this tissue sample as compared with the 9 IDH1 wild-type glioblastoma samples.…”
Section: Discussionmentioning
confidence: 99%